Formulation, evaluation and anti-microbial potential of topical Licorice root extract gel - Amina Al-Nima; Zahraa Qasim; Myasar Al-Kotaji (University of Mosul, 2020)
Objectives: This work aims at formulating licorice as topical gel preparation and at exploring its antimicrobial efficacy against different types of microorganisms including two types of bacteria Staphylococcus aureus (S.aureus), Pseudomonas aeruginosa (P.aerueginosa) and one type of yeast, Candida albicans (C.albicans).Materials and Method: Different gel formulas were prepared using two different types of gelling agent Carbopol 934 and HPMC (methocel E5) with different extract concentrations. All the prepared formulas were physically and chemically characterized, and the selected formula showed good appearance and consistency, spreadability, accepted pH and physiologically compatible to the skin. The selected formula was further characterized by studying the in-vitro antimicrobial activity.Result and Discussion : Results showed that licorice gel can be formulated successfully using Carbopol 934 as gelling agent and the selected formula exhibited good antimicrobial activity against (S.aureus) and (C.albicans), but it showed no antimicrobial activity against (P.aerueginosa). Consequently, the prepared topical gel of licorice could be considered as an efficient alternative to the common topical antimicrobial agents. Furthermore, the results pointed out that the prepared licorice gel has good stability at room temperature with no significant difference (p≤0.05) after storing for four months.Conclusion: In this work a suitable candidate of new herbal antimicrobial topical gel formulation was proposed to enter into the market.